ANALISIS PENDAPATAN USAHATANI DAN SALURAN PEMASARAN JAGUNG MANIS DI KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN KOTA PEKANBARU - Erwin Sinaga; Ahmad Rifai; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this study are: 1) to analyze the level of profit and efficiency of sweet corn farming in Sidomulyo Barat Village, 2) to analyze the level of profit and marketing system of sweet corn in Sidomulyo Barat Village. The sample of farmers in this study amounted to 25 respondents and a sample of traders amounted to 10 respondents. The research method uses census techniques with the overall respondents taking farmers who do sweet corn farming activities. Determination of marketing agency samples using the snowball sampling method by following the marketing channel. The results showed that sweet corn farming efficiency was 1.60 and marketing channel I efficiency was 2.68% and in marketing channel II was 8.55%, the efficient channel was marketing channel I. Farmer channel channel I was 75% and channel II was 69.23% .Keywords: sweet corn, farming, income, marketing channel, farmer share